2015
DOI: 10.3233/jad-142493
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Psychological Distress and Personality Traits on Cognitive Performances and the Risk of Dementia in Patients with Mild Cognitive Impairment

Abstract: Psychological distress negatively affected information processing speed, but was not associated with an increased risk of developing dementia in patients with MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
2
12
0
2
Order By: Relevance
“…Among those with CIND at baseline, we found that conscientiousness was a significant predictor of conversion to dementia, but there was only a non-significant trend for neuroticism. These HRS findings are consistent with a European study of 215 individuals with mild cognitive impairment (Ramakers et al, 2015). The study found that high scores on rigidity, a scale related to conscientiousness, were associated with a lower risk of conversion to dementia.…”
Section: Discussionsupporting
confidence: 92%
“…Among those with CIND at baseline, we found that conscientiousness was a significant predictor of conversion to dementia, but there was only a non-significant trend for neuroticism. These HRS findings are consistent with a European study of 215 individuals with mild cognitive impairment (Ramakers et al, 2015). The study found that high scores on rigidity, a scale related to conscientiousness, were associated with a lower risk of conversion to dementia.…”
Section: Discussionsupporting
confidence: 92%
“…A 10-point increase in neuroticism score values was associated with only 0.15-point decrease in MMSE score at the 10-year follow-up. Paralleling the findings of Ramakers et al [13], the absence of difference in Neuroticism factor and facet scores also concerned the sCON/MCI comparison in our series. It is possible that the very low levels of Neuroticism observed in our sample (compared to age-adjusted normative data) reflect an over-representation of elderly persons with better mental health who are a priori less exposed to the deleterious effect of Neuroticism on cognition.…”
Section: Discussionsupporting
confidence: 72%
“…More recent data challenged the association between high Neuroticism scores and dementia risk. In their 6-year longitudinal study based on the Dutch personality questionnaire, Ramakers et al [13] showed that, although neuroticism scores showed negative correlation with mental speed in MCI, there was no significant association between this variable and MCI conversion to AD. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other indirect converging line of evidence relies on the two personality domains that are similar to LOC — neuroticism (similar to external LOC) vs. conscientiousness (similar to internal LOC). Current literature suggests higher neuroticism and lower conscientiousness predict the incidence of dementia and decline in memory function (Caselli, et al, 2016; Duberstein, et al, 2011; Low, et al, 2013; Ramakers, et al, 2015). Thus, LOC and/or similar traits may serve as phenotypic manifestations of either the function or vulnerability to abnormal brain alterations.…”
Section: Discussionmentioning
confidence: 99%